Probing structure of normal and malignant prostate tissue before and after radiation therapy with luminal water fraction and diffusion‐weighted MRI. Issue 2 (27th December 2018) - Carlin, Dominic; Orton, Matthew R.; Collins, David; deSouza, Nandita M.
Abstract : Background: Interpretation of diffusion in conjunction with T2 ‐weighted MRI is essential for assessing prostate cancer; however, the combination of apparent diffusion coefficient (ADC) with quantitative T2 mapping remains unexplored. Purpose: To document the T2 components and ADC of untreated and irradiated nonmalignant prostate tissue as a measure of their glandular luminal and cellular compartments and to compare values with those of tumor. Study Type: Prospective. Population: Twenty‐four men with prostate cancer (14 untreated; 10 with biochemical recurrence following radiation therapy). Field Strength/Sequences: Endorectal 3 T MRI including a 32‐echo gradient echo and spin echo (GRASE) and an 8 b‐value diffusion‐weighted sequence. Assessment: Regions of interest were drawn on ADC maps and T2 ‐weighted images around focal lesions in areas of biopsy‐positive prostate cancer and in nonmalignant areas of untreated and irradiated peripheral zone (PZ), and untreated transitional zone (TZ). Multiecho T2 data were fitted with mono‐/biexponential decay and nonnegative least squares functions. The luminal water fraction (LWF) was derived. Statistical Tests: The preference between mono‐ and biexponential decay was assessed using the Bayesian information criterion. Differences in fitted parameters between tissue types were compared (paired t ‐test within groups, Kruskal–Wallis and Wilcoxon rank‐sum test between groups) and correlations between ADC and T2 components assessed (Spearman rank correlation test). Results: LWF in tumor (0.09) was significantly lower than in PZ or TZ (0.27 and 0.18, P < 0.01, respectively), but tumor values were comparable to nonmalignant irradiated prostate (0.08). The short T2 relaxation rate was lower in tumor than in nonmalignant untreated or irradiated tissue (significant compared with TZ, P = 0.01). There was a strong correlation between LWF and ADC in normal untreated tissue ( r = 0.88, P < 0.001). This relationship was absent in nonmalignant irradiated prostrate ( r = –0.35, P = 0.42) and in tumor ( r = –0.04, P = 0.88). Data Conclusion: T2 components in conjunction with ADC can be used to characterize untreated and irradiated nonmalignant prostate and tumor. LWF is most useful at discriminating tumor in the untreated prostate. Level of Evidence : 2 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;50:619–627.